FEASIBILITY AND STRATEGIC ANALYSIS OF MARKET ENTRY FOR 3D MAPPING SERVICES IN INDONESIA’S EMERGING SECTOR - Husnia Nur Annisa; Harimukti Wandebori (RADJA PUBLIKA, 2026)
Global advancements in mapping technology contrast with Indonesia’s limited adoption, which remains concentrated in mining and government. As revenue from these sectors declines, PT Geo Indonesia must diversify. This qualitative study examines the feasibility of entering alternative sectors using stakeholder interviews and secondary data. Findings identify three market segments: traditional sectors with slowing demand, emerging engineering sectors facing constraints, and high-potential creative sectors. Analysis reveals favorable external digitalization trends and strong internal technical expertise, despite gaps in marketing and human resources. Application of Porter’s Three Essential Tests confirms that diversification into 3D mapping is attractive and synergistic. The study recommends a dual targeting strategy: prioritizing the creative industry for rapid penetration while building long-term engineering capabilities in architecture, property, and oil and gas. This research provides practical guidance for PT Geo-Indonesia's diversification and market entry strategies in the geospatial sector.